2016
DOI: 10.3354/aei00171
|View full text |Cite
|
Sign up to set email alerts
|

A model for the growth of mariculture kelp Saccharina japonica in Sanggou Bay, China

Abstract: The kelp Saccharina japonica is one of the most important mariculture species in China. To predict kelp growth and provide a component for a general multitrophic ecosystem model, a dynamic individual growth model was developed to evaluate environmental effects on kelp growth. This model was calibrated and validated using data from 2 annual mariculture cycles

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 39 publications
2
37
0
Order By: Relevance
“…This benefits commercial algae species in two ways: It purifies the water, thus increasing water illumination and providing more energy for algal growth, and it prevents phytoplankton from competing with algae for nutrients, which is conducive to the growth and carbon accumulation of cultured algae [ 55 , 56 ]. Through this shellfish–algae interaction, the carbon sink function of the whole integrated culture system is greatly improved, compared with single species cultures [ 57 , 58 ]. Implementation of artificial marine upwelling exchange enhancement project …”
Section: Discussionmentioning
confidence: 99%
“…This benefits commercial algae species in two ways: It purifies the water, thus increasing water illumination and providing more energy for algal growth, and it prevents phytoplankton from competing with algae for nutrients, which is conducive to the growth and carbon accumulation of cultured algae [ 55 , 56 ]. Through this shellfish–algae interaction, the carbon sink function of the whole integrated culture system is greatly improved, compared with single species cultures [ 57 , 58 ]. Implementation of artificial marine upwelling exchange enhancement project …”
Section: Discussionmentioning
confidence: 99%
“…sea surface nitrate, Liu et al 2013) and others that affect the internal state of kelps and their growth (e.g. effective fertilization; Zhang et al 2016b). This is the vital basis to better select suitable sites rapidly and systematically and so to accurately estimate the carrying capacity of a polyculture ecosystem.…”
Section: Site Selection For Phyconomic Activitiesmentioning
confidence: 99%
“…This is the vital basis to better select suitable sites rapidly and systematically and so to accurately estimate the carrying capacity of a polyculture ecosystem. A recent model simulation showed that fertilizing open seawater (with nitrogen) could improve the growth of S. japonica by as much as 4.49, and that dry weight of each frond could increase by 18% after lifting the culture rope to the surface (Zhang et al 2016b). As more data are available, either from satellite imagery or field surveys, GIS-based model predictions will increasingly inform a range of functions as embedded in various components that can be tailored for optimum site selection for economic and environmental phyconomic activities with cultivated kelps.…”
Section: Site Selection For Phyconomic Activitiesmentioning
confidence: 99%
“…For example, line cultivation of Undaria pinnatifida in Spain yielded higher biomass at relatively exposed vs. sheltered sites (Peteiro and Freire, 2011). While in the heavily farmed Sanggou Bay, China, kelp farming is concentrated at the mouth of the bay where nutrient delivery is sufficient relative to within the bay (Shi et al, 2011;Zhang et al, 2016;Wang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%